Impact of Calcium Sources on Soil Chemical Properties, Tomato Growth, Yield, and Quality - Aruna Olasekan Adekiya; Timothy Oyebamiji Ogunbode; Vincent Ishola Esan; Olajire Adedokun; Iyabo Victoria Olatubi; Modupeola Hellen Ayegboyin (The Scientific World Journal, 2025)
Nigerian soils are generally light-textured and have a low cation exchange capacity, crucial for retaining exchangeable cations like calcium, which enhances tomato (Solanum lycopersicum L.) shelf life. Therefore, screenhouse studies were conducted to assess the effects of calcium fertilizers on soil chemical properties and tomato growth, yield, quality, and shelf life. Five Ca fertilizer sources were tested: no fertilizer, calcium sulfate, calcium nitrate, poultry manure, and cow bone biochar. Each was applied at 160 kg Ca ha−1 in a completely randomized design replicated three times. The soil used was classified as Alfisol. Results showed that applying different Ca sources improved soil chemical properties (organic matter, N, P, K, Ca, and Mg), plant growth (height and stem diameter), yield (fruit number and weight), and the mineral content of tomatoes. Results showed that calcium sulfate increased the Ca content of the soil by 1.25%, 9.82%, 20.11%, and 704% compared to calcium nitrate, poultry manure, biochar, and the control, respectively. Poultry manure enhances growth and yields the most due to its balanced nutrient supply. Poultry manure increased plant height by 10.1%, 11.2%, 20.3%, and 45.2% compared to calcium nitrate, calcium sulfate, biochar, and the control, respectively. Similarly, tomato fruit yield increased by 22.5%, 20.16%, 83.4%, and 382.5% relative to calcium nitrate, calcium sulfate, biochar, and the control, respectively. Relative to calcium nitrate, poultry manure, biochar, and control, calcium sulfate treatment reduced weight loss of tomato by 24.81%, 55.59%, 61.19%, and 104.99% and increased shelf life by 14.78%, 29.79%, 36.42%, and 69.44%, respectively. This effectiveness was attributed to its high Ca content. While poultry manure was effective in enhancing tomato yield and quality, it was not as effective as calcium sulfate in extending shelf life and reducing weight loss. Thus, future research should focus on the potential integration of poultry manure with calcium sulfate to develop an amendment that could improve yield, quality, and shelf life of tomatoes.